Picie kontrolowane – propozycja strategii pomocowych dla młodych dorosłych - Dolata, Dorota (Kultura-Społeczeństwo-Edukacja, 2014)
As statistics in Poland show, more and more younger people reach for alcohol and, what is more, they struggle to control their drinking. This often leads to a number of serious consequences for all health, economic, psychological, and social ones. They include beatings, injuries, loss of material property or even conflict with the law. Uncontrolled chemical intoxication may even lead to the long-term consequences which is e.g. addiction to alcohol. In some countries, they apply a form of assistance to people drinking in a risky way, and not only to them, which is aimed at the acquisition of skills for controlling alcohol consumption. There are used a number of methods and progressive stages of dealing with the client, so that he or she would learn controlled drinking. Therefore, not only this article briefly presents the causes and mechanisms of addiction resulting in the wide range of consequences, but also is the proposal for a strategy of assistance for young adults focused on the acquisition of skills in controlling the use of alcohol, as well as shows the results of the effectiveness of this form of assistance in some countries in the world.